PENGARUH EKSTRAK DAUN SIRIH MERAH (Piper crocatum) TERHADAP PERTUMBUHAN CANDIDA ALBICANS - sri Rezeki; Santi Chismirina; Aulia Iski (Journal of Syiah Kuala Dentistry Society, 2017)
AbstractThe treatment of oral candidiasis commonly used antifungal drug synthesis, but it has some effects such as nausea, vomiting, diarrhea, and headache. The leaves of red betel (Piper crocatum) have several compounds which act as antifungals such as alkaloids, tannins, saponins, and flavonoids. The purpose of this study was to determine the effect of Minimum Inhibitory Concentration (MIC) and Minimum Kill Concentration (MBC) Piper crocatum leaves with a concentration of 25%, 50%, 75%, and 100% to the growth of Candida albicans. This study is a laboratory experimental which is designed by posttest only control group using the extract of leaves of Piper crocatum. The leaves are extracted by maceration method using 96% of ethanol. The extraction results obtained diluted to be a concentration of 25%, 50%, and 75%. The extract has been tested phytochemical, were tested for antifungal activity using dilution method with Standard Plate Count (SPC) in SDA media. The result of one-way ANOVA analysis showed that the extract of Piper crocatum leaves affected the growth of C. Albicans with p = 0.00 (p0.05). 25%of the extract concentration can inhibit the growth of C. albicans From the results of this study concluded that the extract of Piper crocatum leaves affected the growth of C. Albicans with MIC at a concentration of 25% and MBC at 100% concentration of the extract of Piper crocatum.Keyword: Red bettle (Piper crocatum), Candida albicans, antifungal, dilution method.